New mutation to Huntington's disease. Issue 1 (January 1989) - Wolff, G; Deuschl, G; Wienker, T F; Hummel, K; Bender, K; Lücking, C H; Schumacher, M; Hammer, J; Oepen, G
Abstract : We report a large family with an isolated case of Huntington's disease (HD), which is probably the result of a new mutation. The patient developed clinical signs typical of HD at the age of 36. The clinical course of the patient's disease is documented by several clinical admissions over a period of 14 years at present. The family history is strikingly negative with the parents having been clearly unaffected into their 80s and with 13 older and two younger, living, healthy sibs. Extensive testing of polymorphic markers (blood groups, red cell and serum proteins, HLA antigens) showed no indication of non-paternity, but rather gave strong support to the hypothesis that the proband is a full sib. In addition, DNA typing for several RFLPs known to be closely linked to the HD gene locus indicated that several clearly unaffected sibs share one or the other or both of the patient's haplotypes. This is further evidence in favour of the hypothesis of a new mutation at the HD locus. The posterior probability of a new mutation to HD in the patient exceeds 99%, even if an a priori probability of non-paternity of 10% and a mutation rate of HD of 10(-7) is assumed.